Optimizing the Use of Wordwall Educational Games Aplication - Arthaningtyas, Kun; Nurmayanti, Nita; Malia, Jamil; Tabroni, Imam; Zou , Guijiao; Jonathan, Bouyea (Journal Emerging Technologies in Education, 2023)
Background. Wordwall is an interesting application associated with this program. The app is clearly intended as an educational tool, a platform and an exhilarating evaluation for students. Teachers find it suitable with the concept of learning and playing using wordwall during student learning to keep it interesting and avoid boredom Purpose. Wordwall media can increase happiness, excitement, enthusiasm and motivation. Method. This wordwall can be used for all levels of online and offline learning, from elementary school to college. Results. , Its simple design and many features, Wordwalls is very easy for new users to understand, Wordwalls has several advantages, Wall is very special compared to other web applications. Conclusion. The use of word walls in the learning process is not yet common, but there are many documents and research results about word walls on the Internet. Using phallus words by students in online learning, it was concluded that phallus words can improve students' learning activities and outcomes. The text wall increases students' interest in the lesson and reduces boredom during the teaching process